ESTIMATION OF WATER BALANCE PARAMETERS IN ROGERM CATCHMENT AREA, MANGESH, DUHOK GOVERNORATE, KURDISTAN REGION OF IRAQ - AL-DOSKY, HALIZ SALEEM MOHAMMED ALI (Journal of Duhok University, 2022)
The analysis of some hydrological elements of the water balance of Rogerm catchment area which is in Mangesh subdistrict, Duhok Governorate about 45 km north-west of Duhok was conducted. The aimed area is around 179.5 km². The historical record of rainfall data in Mangesh Agricultural office stations were used to calculate the water balance parameters for the period 2012-2013 to 2020-2021. The average amount of rain is almost 783.5 mm, it falls through 56 days of eight rainfall months/year. The biggest amount of rain falls in March, it reaches 158.4 mm. In winter the rain is denser and it reaches 47.7% from the total of the rainy year. 46.1% of the total amount of rain falls during two days, which cause the surface runoff. Water surplus was between 77% - 78% and 18% ground water recharge of the total annual rainfall. The probability of return period of the water surplus each two years may be 50% from (565-907 mm/year) and 50% from (363-530 mm/year) consequently, while maximum and minimum probability of return period is (907 mm/year) and (363 mm/year) consequently of the water surplus for the coming year are 10% and 90% consequently